2013
DOI: 10.1039/c3ib40103k
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer normalization induced by embryonic mesenchyme is mediated by extracellular matrix biglycan

Abstract: Some epithelial cancers can be induced to revert to quiescent differentiated tissue when combined with embryonic mesenchyme; however, the mechanism of this induction is unknown. Here we combine tissue engineering, developmental biology, biochemistry and proteomics approaches to attack this problem. Using a synthetic reconstitution system, we show that co-culture of breast cancer cells with embryonic mesenchyme from early stage (E12.5-13.5) mammary glands decreases tumor cell proliferation while stimulating aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
4
26
0
Order By: Relevance
“…Indeed, high levels of biglycan expression are associated with increased risk of esophageal squamous cell carcinoma [157], significant clinical outcome of pancreatic adenocarcinoma [167], enhanced gastric cancer invasion [183], and breast cancer normalization [184]. It is well established that breast cancer cells slow their growth and differentiate when associated with embryonic mesenchyme.…”
Section: Biglycan Triggers Inflammation and Tumorigenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, high levels of biglycan expression are associated with increased risk of esophageal squamous cell carcinoma [157], significant clinical outcome of pancreatic adenocarcinoma [167], enhanced gastric cancer invasion [183], and breast cancer normalization [184]. It is well established that breast cancer cells slow their growth and differentiate when associated with embryonic mesenchyme.…”
Section: Biglycan Triggers Inflammation and Tumorigenesismentioning
confidence: 99%
“…Notably, when the matrix secreted by embryonic mammary mesenchyme was injected into fast-growing breast carcinoma in mice, there was a marked reduction of growth. Proteomics analysis of this mesenchyme ECM showed biglycan as a major constituent [184]. Moreover, addition of soluble biglycan was capable of evoking the tumor normalization response, and RNAi-mediated depletion of biglycan expression in cultured embryonic mesenchyme abolished the ECM’s inductive activity [184].…”
Section: Biglycan Triggers Inflammation and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow stromal cell-derived biglycan may have similar anti-bone metastatic functions as decorin. Biglycan in an ECM scaffold produced by mammary mesenchyme cells can “normalize” breast cancer cells in vitro [34]. In addition, decreased biglycan is found in paired bone metastases compared to primary tumors in breast cancer patients [35].…”
Section: Small Leucine-rich Proteoglycans (Slrps)mentioning
confidence: 99%
“…Ingber (Harvard University, Cambridge, MA, USA) emphasized in a keynote presentation the importance of the tumor microenvironment and showed that local changes in extracellular matrix (ECM) remodeling and cell mechanics actively contribute to tumor initiation and progression. He also showed that breast cancer cell growth and spheroid architecture are normalized when mixed with normal embryonic mesenchyme or with the critical ECM component biglycan in either 3D Matrigel or in collagen I gels (1). This insight on the tumor microenvironment was applied in the context of human ‘organs-on-chips’: cell culture devices containing micrometer-sized chambers seeded with live cells that then recapitulate the specialized multicellular architectures, tissue-tissue interfaces, physicochemical microenvironments, and vascular perfusion necessary to capture complex organ-level functions and human disease processes in vitro (2), (3).…”
Section: Presentation Summariesmentioning
confidence: 99%